Case report: Disease phenotype associated with simultaneous biallelic mutations in ABCA4 and USH2A due to uniparental disomy of chromosome 1 - Villafuerte-De la Cruz, R.; Chacon-Camacho, O. F.; Rodriguez-Martinez, A. C.; Xilotl-De Jesus, N.; Arce-Gonzalez, R.; Rodriguez-De la Torre, C.; Valdez-Garcia, J. E.; Rojas-Martinez, A.; Zenteno, J. C. (Frontiers in Genetics, 2022)
Inherited retinal diseases (IRDs) represent a spectrum of clinically and genetically heterogeneous disorders. Our study describes an IRD patient carrying ABCA4 and USH2A pathogenic biallelic mutations as a result of paternal uniparental disomy (UPD) in chromosome 1. The proband is a 9-year-old girl, born from non-consanguineous parents. Both parents were asymptomatic and denied family history of ocular disease. Clinical history and ophthalmologic examination of the proband were consistent with Stargardt disease. Whispered voice testing disclosed moderate hearing loss. Next-generation sequencing and Sanger sequencing identified pathogenic variants in ABCA4 (c.4926C>G and c.5044_5058del) and USH2A (c.2276G>T). All variants were present homozygously in DNA from the proband and heterozygously in DNA from the father. No variants were found in maternal DNA. Further analysis of single nucleotide polymorphisms confirmed paternal UDP of chromosome 1. This is the first known patient with confirmed UPD for two recessively mutated IRD genes. Our study expands on the genetic heterogeneity of IRDs and highlights the importance of UPD as a mechanism of autosomal recessive disease in non-consanguineous parents. Moreover, long-term follow-up is essential for the identification of retinal features that may develop as a result of USH2A-related conditions.